Study and Analysis of Raw Water and Drinking Water in Garma District, Anbar Province, Iraq - Bashar Abdulazeez Mahmood (Journal of Global Pharma Technology, 2018)
The study included physical, chemical and biological laboratory measurements of raw water and potable water in Garma district in Anbar province in several areas (Central Garma, New Garma, Sabihat, Sabihat 1, Sabihat 2, Al-Sager, Al-Habib, AlBukhlifa, Al Busheihan, Abautai, Karagul, Dwaya, Buakakul). A comparison was made between the values of the laboratory-measured variables and their measured values in the Directorate of the Central Garma Water Project as well as their comparison with the Iraqi and international standards for drinking water. The modeling process began in September 2017 until March 2018. The study includes physical measurements (temperature, electrical conductivity, turbidity, suspended solids and dissolved solids) and chemical measurements of (pH and positive ions calcium, magnesium, sodium, potassium and Negative ions sulphates, chlorides, and total hardened bases) and biological measurements (Mcount1). The study showed variation in values from the Iraqi and international standard limits where there was an increase in the values of electrical conductivity and concentration of magnesium and sulphate. The rest of the values did not exceed the standard values. Linear and back linking and correlations between chemical and physical measurements of different water models were also found for all study areas using SPSS.